The facilitative role of listener’s pointing gestures in collaborative tasks - Sekine, Kazuki; Kanemaru, Kotaro; Kadota, Keisuke (Frontiers in Communication, 2025)
We investigated the role of listener-produced pointing gestures in a collaborative sticker localisation task. While previous research has emphasised the communicative value of speaker gestures, few experimental studies have examined how listeners’ gestures shape interaction. We examined how listeners’ gestures facilitate interaction, using a two-by-two within-subjects design that manipulated whether speakers were allowed to gesture and whether listeners began trials with a pointing gesture. Forty-eight adults participated in a sticker localisation task, and three dependent measures were analysed: task completion time, the number of spatial utterances, and gesture duration. The results demonstrated that listeners’ pointing gestures significantly reduced task duration, regardless of whether the speaker gestured. Additionally, these listener gestures prompted longer gestural output by the speakers, suggesting that visible bodily engagement from listeners influenced speakers’ multimodal behaviour. By contrast, speaker gestures did not significantly affect efficiency. These findings provide empirical support for the idea that listeners’ gestures function as participatory and epistemic actions, not merely as passive cues of understanding. The study supports a reciprocal model of gesture, demonstrating that both speakers and listeners use bodily actions to co-construct spatial reference. By providing experimental evidence on listener gestures, it contributes to research that frames gesture as an interactive and embodied process. These findings also suggest potential applications for designing collaborative systems that respond to real-time bodily cues.